Development of Self-Regulated Learning Model based on Class Dojo Application (Digital Portfolio) in improving Student Achievement - Hijrah, Hijrah; Hafid, Hilda; Saiful, Saiful (Institut Agama Islam Negeri Palopo, 2023)
The aim of the research is to find out how the process enhancing students’ achievement by using Portofolio mobile Apps Portofolio based called Class Dojo to Junior High School Students worked. Research and Development method was applied by using three common steps in RnD; first step is the introduction where the researcher analyze the problems and collecting first data related to Self-Regulated Learning to the subject research; the next step is adjusting and develop the new model to the old learning process; and the last step is the evaluation process to assess the whole development applied in this research. It can be cocnluded that the development of learning aided by Class Dojo Application can improve students' self-regulated learning ability. There is an increase in student learning outcomes which means that it has met the specified success criteria. The increase has an impact on improving the quality of learning, in this case, learning resources increase with increasingly varied learning media, so that it can help teaching students.